Unintended pregnancies: a comprehensive cost–benefit analysis of family planning investment in Pakistan - Irum, Aisha; Naz, Olan; Ibrahim, Muhammad; Khan, Adnan Ahmad (Frontiers in Public Health, 2025)
IntroductionUnintended pregnancies, which account for 19.4 to 38.2% of all births, present a significant and pressing public health challenge in Pakistan. Beyond the adverse effects of women’s agency and choice, unsafe abortions, delayed prenatal care, and poor maternal health, they impose substantial economic costs on essential services such as education, healthcare, water, sanitation, and housing infrastructure. We quantified the economic cost of unintended pregnancies and the benefits of investing in family planning. Our findings directly challenge the rationale behind population-based revenue distribution formulas and provide compelling economic evidence for increased family planning budget allocations at both national and provincial levels.MethodologyThis secondary data analysis employs a rigorous methodology, triangulating data from various national and international sources to conduct a comprehensive cost–benefit analysis. Using trend analysis with linear extrapolation, the study projects the economic impact of unintended pregnancies from 2018 to 2035 across key domains, such as schooling, immunization, safe motherhood, and access to safe water and sanitation. Key variables include contraceptive prevalence rate, unmet need for family planning, general fertility rate, under-five mortality rates, social costs per child, school enrollment rates, and per-user cost of family planning.ResultsOur analysis reveals that the additional programming costs in health, education, and water provision from unintended pregnancies outweigh the investment required for family planning interventions aimed at averting them. Specifically, for every dollar invested in family planning, there is an estimated return of approximately USD 23 in combined cost savings. Education costs represent the largest proportion (51%) of these savings, followed by safe motherhood costs (36%), immunization costs (11%), and water/sanitation costs (2%).ConclusionWe show substantial cost savings from investing in family planning. Some provincial governments have argued that since national revenue distribution is population-based, they would lose funds if they instituted FP programs. We show that these losses are in a few percentage points while their cost savings in social programs would be in hundreds of percentage points while achieving healthier and flourishing populations. Cost–benefit analysis is a powerful tool for policymakers and may be institutionalized in health, population, planning, and finance ministries.